MICROBIOTA INSIGHTS IN CLOSTRIDIUM DIFFICILE INFECTION AND INFLAMMATORY BOWEL DISEASE. Issue 1 (9th November 2020) - Rodríguez, C.; Romero, E.; Garrido-Sanchez, L.; Alcaín-Martínez, G.; Andrade, RJ.; Taminiau, B.; Daube, G.; García-Fuentes, E.
ABSTRACT: Inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation that includes Crohn´s disease (CD) and ulcerative colitis (UC). Although the etiology is still unknown, some specific factors have been directly related to IBD, including genetic factors, abnormal intestinal immunity, and/or gut microbiota modifications. Recent findings highlight the primary role of the gut microbiota closely associated with a persistent inappropriate inflammatory response. This gut environment of dysbiosis in a susceptible IBD host can increasingly worsen and lead to colonization and infection with some opportunistic pathogens, especially Clostridium difficile. C. difficile is an intestinal pathogen considered the main cause of antibiotic-associated diarrhea and colitis and an important complication of IBD, which can trigger or worsen an IBD flare. Recent findings have highlighted the loss of bacterial cooperation in the gut ecosystem, as well as the pronounced intestinal dysbiosis, in patients suffering from IBD and concomitant C. difficile infection (CDI). The results of intestinal microbiota studies are still limited and often difficult to compare because of the variety of disease conditions. However, these data provide important clues regarding the main modifications and interrelations in the complicated gut ecosystem to better understand both diseases and to take advantage of the development of new therapeutic strategies. In this review, we analyze in depth the gut microbiota changes associated with both forms of IBD and CDI and their similarity with the dysbiosis that occurs in CDI. We also discuss the metabolic pathways that favor the proliferation or decrease in several important taxa directly related to the disease.